Differences in human perception - Alireza Mahdizadeh Hakak; Joydeep Bhattacharya; Nimish Biloria; Roy de Kleijn; Fanak Shah- Mohammadi (A+BE: Architecture and the Built Environment, 2018)
Spatial navigation involves dynamic and intricate brain functions, fundamentally required to locate oneself in space, which is vital for any human’s survival in their daily life. Sensorimotor abilities are quintessential for spatial navigation wherein subjects associate external sensory stimuli with sensori commands. Individuals for instance process external stimiuli such as buildings in the environment and pathways between the buildings and internally create spatial information in their brain and use this information to navigate in the environment (Brunsdon, Nickels, & Coltheart, 2007; Davis, 1999; Farah, 1989). Therefore, individuals create a mental image of the environment which they are navigating and with respect to their target, they manipulate their current position (Palermo, Iaria, & Guariglia, 2008).